Land Law Reform in Indonesia and Nigeria: Towards Equitable Agrarian Governance - Damanik, Pandapotan; Nnawulezi, Uche (Batulis Civil Law Review, 2025)
Introduction: Land inequality remains a major challenge in developing nations, particularly in Indonesia and Nigeria, where unequal land distribution has deep social and economic implications. Both countries have undertaken land law reforms to promote fair access and sustainable resource management. Understanding how these reforms operate within distinct legal and historical contexts is essential for achieving equitable agrarian governance.Purposes of the Research: Analyze and compare the land law reform processes in Indonesia and Nigeria to assess their contribution to achieving justice in agrarian governance. It seeks to identify key similarities and differences in reform approaches, evaluate their socio-legal impacts, and explore policy strategies that strengthen land rights, social inclusion, and rural welfare.Methods of the Research: A qualitative comparative legal analysis was employed, focusing on legal frameworks, policy implementation, and institutional mechanisms in both countries. Data were collected through literature review, document analysis, and secondary sources such as academic journals and government reports. The comparative framework allows examination of each country’s reform trajectory and its effectiveness in promoting fair and sustainable agrarian governance.Results Main Findings of the Research: The findings reveal that although both countries differ in their historical and legal contexts, they face similar challenges namely, land ownership concentration among economic elites and weak protection of indigenous and smallholder farmers’ rights. Indonesia has shown progress through land redistribution and asset legalization programs, while Nigeria emphasizes decentralized land management and community-based access policies. The study concludes that achieving equitable agrarian governance depends on the integration of legal reform, public participation, and policy transparency.